Pemberdayaan Masyarakat untuk Dukung STBM: Pembuatan Kloset, Edukasi Stop BABS, dan CTPS: Pengabdian - Risnawati Tanjung; Jernita Sinaga; Mustar Rusli; Helfi Nolia; Deli Syaputri; Marganda Halomoan Manalu (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
STOP BABS (Stop Defecating in the Open) and CTPS (Washing Hands with Soap) are part of the 5 pillars of STBM (Community-Based Total Sanitation). Open defecation is a serious threat to health and sanitation dignity. Washing hands can prevent infectious diseases and around 80% of all cases of infectious diseases can also be transmitted through hand contact. Making a bowel toilet seat is an essential first step in providing proper sanitation facilities. The right design and high-quality manufacture of the toilet seat can improve user comfort and safety, and help reduce the risk of contamination. The purpose of this activity is Community Empowerment in Making Bowel Toilet Seats and Education to Stop BABS (Defecation in the Open), CTPS to Support the STBM Program in Parbuluan VI Village, Parbuluan District, Dairi Regency. Increasing community knowledge regarding STBM, especially STOP BABS and getting people used to CTPS. The implementation method is the distribution of pre- and post-test questionnaires. Knowledge about Washing Hands with Soap to support STBM and making toilet seat bowels is seen in 83% good category, attitude about STOP BABS (Open Defecation), Washing Hands with Soap (CTPS) to support STBM program and Skills in Making Toilet Seat Bowel has good attitude of 87%, Participant skills are 80% good.